1995
DOI: 10.1161/01.atv.15.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombosis–Associated Inflammation and Attenuation With Neutralizing Antibodies to Cytokines and Adhesion Molecules

Abstract: Thrombosis and inflammation are closely related. However, the response of the vein wall to venous thrombosis has been poorly documented. This study examines the hypothesis that venous thrombosis is associated with an inflammatory response in the vein wall. In a rat model of inferior vena caval thrombosis, vein wall was temporally examined for inflammation by assessment of histopathology, leukocyte morphometrics, and cytokine levels. Animals were killed 1 hour and 1, 3, and 6 days after thrombus induction. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 61 publications
10
159
1
Order By: Relevance
“…Whereas other studies have suggested the early DVT environment is proinflammatory (4,5,8), the data herein support several mechanisms associated with CCR2 signaling activity that directly affects thrombus resolution (Fig. 6).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Whereas other studies have suggested the early DVT environment is proinflammatory (4,5,8), the data herein support several mechanisms associated with CCR2 signaling activity that directly affects thrombus resolution (Fig. 6).…”
Section: Discussionsupporting
confidence: 59%
“…Although four main chemokine families exist, the ones most relevant to DVT resolution are the cysteine-cysteine (CC) and cysteine-X-cysteine (CXC) chemokine types. For example, both CXC and CC chemokines are present within a resolving thrombus (4), and exogenous administration of IL-8 (CXC chemokine) and MCP-1 (a CC chemokine) have been shown to accelerate thrombus resolution in experimental models (7,8). Many pathophysiological processes involve CCR2 signaling, including peritoneal and pulmonary inflammation, and atherogenesis (9 -11).…”
Section: Eep Vein Thrombosis (Dvt)mentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies were performed using a rat model of stasis induced venous thrombosis (Wakefield et al 1995). The protocol was approved by the University of Michigan Committee on the Use and Care of Animals and strictly complied with the National Institutes of Health Guide for the Care and Use of Laboratory Animals.…”
Section: Animal Methodsmentioning
confidence: 99%